Quantifying the gradients exposed to a professional golfer during a round of golf - Peters, R.; Smith, N.; Lauder, M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Research has suggested that that when performing a tee shot a gradient slope of 4.4% (2.25°) and above it is noticeable to the golfer and may cause an adjustment to their normal stance (Linde, 2005). To quantify what gradients were exposed to a golfer during a round of golf an inclinometer was utilised to measure the gradient of shots in open play from around 16 golf courses across the UK. Twenty two right handed male professional golfers were recruited and the inclinometer was placed between the inside of the feet and the ball. The results showed that over 50% of shots where performed on an incline greater than 2.25° mainly ranging from 0 to (+/-) 10°. These results suggest that future research is required to investigate the effects of gradient on the mechanics of the golf swing.